Anti-cancer activity of Cedrus deodara in 1,2- dimethly hydrazine (DMH) induced anti cancer model in rats - Sharma, Amit; Arora, Pankaj (Asian Journal of Pharmaceutical Research and Development, 2018)
Cancer is a dangerous disease of all multicellular organisms. Cancer is a serious as well as life threatening disease characterized by uncontrolled division and growth of abnormal cells in the body. In present study anti cancer potential of traditional herbal Cedrus deodara were studied in 1,2- dimethly hydrazine (DMH) induced anti cancer model. Various biochemical parameters were evlautaed such as Alakaline phosphate, Aspartate aminotransferase, Alanine aminotransferase and Histology of Liver tissue were examined. Data of the study revealed that significant depletion of biochemical markers in DMH-untreated rats as compared with control rats throughout the experimental period. This depletion might because the extract treated group shows improvement level in rats treated with DMH showed significant decrease, as a result levels of antioxidant enzymes decreased. Also DMH produces free radicals in blood, liver and the large intestine of experimental models .